Application of the Snowball Throwing Learning Model in Improving the Results and Learning Interest of Students at Pasirkuntul Elementary School - Euis Latipah; Lisda Aulia Apriani; Silvi Sofiatul Alawiyah; Tri Fatmah Nurhalizah (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aims to describe in detail the application of the Snowball Throwing learning model by researchers directly in improving learning outcomes and learning interests of students at SDN Pasirkuntul. This learning model was chosen because it has active, fun characteristics, and encourages direct student involvement in the learning process. Snowball Throwing provides space for students to be actively involved in conveying and receiving information dynamically through throwing "snowballs" containing questions and answers that they create themselves. This study uses a descriptive qualitative approach, where researchers play a direct role as teachers who design, implement, and reflect on the learning process by applying the model. The subjects of the study were approximately 30 grade VI students. Data collection techniques include participatory observation, field notes, teaching reflections, and documentation of student learning outcomes obtained during the learning process. The results of the study indicate that the direct application of the Snowball Throwing model can increase student activity in learning activities in the classroom. In addition, there was an increase in enthusiasm, enthusiasm, and interest in learning for students as seen from their active involvement in discussions, answering questions, and group collaboration. The application of this model also creates a more lively and communicative learning atmosphere. Thus, Snowball Throwing can be an alternative effective, innovative, and fun learning strategy to improve students' learning outcomes and interests at elementary school level, especially in presenting student-centered learning.